The Relationship between Disclosure of Corporate Social Responsibility and Financial Performance: Empirical Evidence from Chemical Industry in Shanghai Stock Exchange - Li, Dandan (2019)
With the development and progress of Chinese society and the rapid spread of information, Chinese chemical companies are constantly experiencing scandalous events such as dangerous chemical spills, water pollution and other phenomena of social interests. This links with the performance of the corresponding social responsibility. These events have spurred people's attention and awareness of corporate social responsibility (CSR). Due to the recent scandals, some enterprises in China pay more and more attention to CSR while paying attention to operating profits. Based on the current research status, this paper proposes the research theme to study the impact of CSR information disclosure on business performance.